The first African Anthracoptilidae (Insecta: Paoliida) near the Permian—Triassic boundary in Kenya - Nel, Andre; Garrouste, Romain; Prokop, Jakub (Zootaxa, 2015)
The first findings of Antracoptilidae (Paoliida) from the Late Permian/ Early Triassic of Africa, i.e. the new genus Afrocladus comprising A. pumilio sp. nov. and A. kenyaensis sp. nov., are described from the Mombasa Basin of Maji ya Chumvi Formation in Kenya (Duruma sandstones). Both diagnoses are based on wing venation pattern. Their occurrences close to the P–T boundary possibly indicate the last appearence date of the group being known since early Pennsylvanian. Moreover, their significantly smaller wing sizes compared to known taxa suggest adaptations to different habitats and environmental conditions or different life strategy.